2007
DOI: 10.1007/s00248-007-9347-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel Archaea and Bacteria Dominate Stable Microbial Communities in North America’s Largest Hot Spring

Abstract: Boiling Springs Lake is an approximately 12,000 m(2), 55 degrees C, pH 2 thermal feature located in Lassen Volcanic National Park in northern California, USA. We assessed the microbial diversity in the lake by analyzing approximately 500 sequences from clone libraries constructed using three different primer sets targeted at 16S rRNA genes and one targeted at 18S rRNA genes. We assessed the stability of the microbial community by constructing terminal restriction fragment length polymorphism (T-RFLP) profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 55 publications
1
44
0
Order By: Relevance
“…As documented previously in Thailand's Bor Khlueng neutral pH hot spring systems (50-57°C), members of major phyla were well represented in the P1, P2, and P3 samples (Kanokratana et al, 2004). Similarly, bacteria of high abundance (Aquificales, Nitrospira, and Thermodesulfobacterium) detected during this study were also shown to be major constituents in nearby sulfide-rich and silica-depositing Icelandic hot springs that were alkaliphilic (pH 8-10) and thermophilic (*65°C) (Tobler and Benning, 2011), as well as in other silica-precipitating hot springs in New Zealand (Childs et al, 2008), Japan (Yamamoto et al, 1998), and the USA (Blank et al, 2002;Wilson et al, 2008). In Hverager+i wastewater drain sample with a temperature of about 70°C, Aquificae represented about 11% of OTUs (Tobler and Benning, 2011).…”
Section: Discussionsupporting
confidence: 66%
“…As documented previously in Thailand's Bor Khlueng neutral pH hot spring systems (50-57°C), members of major phyla were well represented in the P1, P2, and P3 samples (Kanokratana et al, 2004). Similarly, bacteria of high abundance (Aquificales, Nitrospira, and Thermodesulfobacterium) detected during this study were also shown to be major constituents in nearby sulfide-rich and silica-depositing Icelandic hot springs that were alkaliphilic (pH 8-10) and thermophilic (*65°C) (Tobler and Benning, 2011), as well as in other silica-precipitating hot springs in New Zealand (Childs et al, 2008), Japan (Yamamoto et al, 1998), and the USA (Blank et al, 2002;Wilson et al, 2008). In Hverager+i wastewater drain sample with a temperature of about 70°C, Aquificae represented about 11% of OTUs (Tobler and Benning, 2011).…”
Section: Discussionsupporting
confidence: 66%
“…The other dominant OTUs within Betaproteobacteria were OTU 128, 1320 and 940 were classified under the order Burkholderiales, Thiobacterales and Hydrogenophilales respectively (Additional file 1: Table S1). Previous studies show the predominance Proteobacteria , particularly of Betaproteobacteria in a circumneutral hot spring from the Uzon Caldera, Kamchatka, Russia (Wemheuer et al 2013; Chan et al 2015) and other acidic thermal springs (Wilson et al 2008). The information on distribution of genera is listed in Additional file 1: Table S2.…”
Section: Resultsmentioning
confidence: 93%
“…BSL is an acidic, high temperature lake (ranging between 52°C and 95°C, with a pH of approximately 2.5), which sustains a purely microbial ecosystem comprised of novel Archaea, Bacteria and several species of unicellular Eukarya [21,22]. …”
Section: Resultsmentioning
confidence: 99%